A Chimeric DNA/RNA Antiparallel Quadruplex with Improved Stability. Issue 2 (1st February 2022) - Boyle, Elaina P.; Lomidze, Levan; Musier‐Forsyth, Karin; Kankia, Besik
Abstract: Nucleic acid quadruplexes are proposed to play a role in the regulation of gene expression, are often present in aptamers selected for specific binding functions and have potential applications in medicine and biotechnology. Therefore, understanding their structure and thermodynamic properties and designing highly stable quadruplexes is desirable for a variety of applications. Here, we evaluate DNA→RNA substitutions in the context of a monomolecular, antiparallel quadruplex, the thrombin‐binding aptamer (TBA, GGTTGGTGTGGTTGG) in the presence of either K + or Sr 2+ . TBA predominantly folds into a chair‐type configuration containing two G‐tetrads, with G residues in both syn and anti conformation. All chimeras with DNA→RNA substitutions (G→g) at G residues requiring the syn conformation demonstrated strong destabilization. In contrast, G→g substitutions at Gs with anti conformation increased stability without affecting the monomolecular chair‐type topology. None of the DNA→RNA substitutions in loop positions affected the quadruplex topology; however, these substitutions varied widely in their stabilizing or destabilizing effects in an unpredictable manner. This analysis allowed us to design a chimeric DNA/RNA TBA construct that demonstrated substantially improved stability relative to the all‐DNA construct. These results have implications for a variety of quadruplex‐based applications including for the design of dynamic nanomachines. Abstract : DNA→RNA substitutions in the context of a monomolecular, antiparallel quadruplex, the thrombin binding aptamer (TBA) have been investigated in the presence of either K + or Sr 2+ . Analysis of the stabilizing and destabilizing influences allowed to design a chimeric DNA/RNA TBA construct that demonstrated substantially improved stability relative to the all‐DNA construct.